Forehand Technique in Court Tennis - Raymond Pardamean Tamba; Yehezkiel Chalvin Ginting; Opsor Sipayung; Indah Khusnul Khotimah; Nurkadri Nurkadri (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objectives. Good forehand techniques are essential for athletes and players looking to improve their game. By developing a strong forehand, players can achieve greater consistency, reach the ball further, and maintain better court positioning. The mastery of different forehand techniques, such as topspin or slice forehand, provides players with a wider range of strategic options during gameplay. By mastering these techniques and incorporating them into their gameplay, athletes, and players can take their performance to the next level. Materials and methods. To prepare for a game of tennis, certain materials such as a tennis court, rackets, balls, and appropriate clothing and shoes are required. The warm-up session should include running around the tennis court for two laps followed by static and dynamic stretching. To improve one's forehand technique, it is recommended to watch tutorials on YouTube to understand the contact point of the ball, the position of the feet, how to hold the racket, and the twist or rotation of the body while hitting the forehand. For beginners, it is best to start with basic drill techniques like shadow forehand to practice forehand movements without hitting the ball or flat-hit drills with a softball. Once the basic drills are mastered, one can move on to drill variations. Results. Enhancing the forehand technique is crucial for achieving consistency and accuracy in tennis. Precision can be improved by optimizing the ability to send the ball toward the target with greater efficiency. Practicing the shadow drill is an effective method to increase the strength of the forehand stroke. Consequently, the player will be able to exert more force and achieve greater ball speed. In addition, rotating the ball in the desired direction can be achieved through proper technique and body positioning. Conclusion. This specialized training program offers a multitude of benefits that can enhance the skills and performance of players and athletes. By emphasizing the improvement of forehand technique, the program can effectively enhance accuracy, strength, ball rotation, agility, self-assurance, and adaptability when executing forehand technique during gameplay.